Ethics in AI-Based Sustainability Accounting to Support SDGs: An ADO Model Approach - Handayani, Susi; Soewarno, Noorlailie (Universitas Gorontalo, 2026)
This article analyzes the literature on artificial intelligence (AI) ethics in sustainability accounting and its contribution to the Sustainable Development Goals (SDGs). The study employs a Systematic Literature Review (SLR) approach based on the Antecedents, Decisions, and Outcomes (ADO) framework, which has rarely been applied to this topic. Data were obtained from the Scopus database, consisting of 57 articles published between 2020 and 2025. The findings indicate that AI has the potential to support sustainable development through effective risk management and the implementation of green innovation. Green innovation acts as a mediating variable between the application of AI in sustainability accounting and the achievement of the SDGs. In addition, industry competitiveness and environmental uncertainty serve as moderating factors influencing the effectiveness of AI implementation. Overall, the implementation of AI in sustainability accounting can enhance organizational reputation, strengthen stakeholder loyalty, and create competitive advantage.